PENDAMPINGAN HUKUM TERHADAP KORBAN MARITAL RAPE DITINJAU DARI UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA (Studi Kasus di Women Crisis Center Mawar Balqis Cirebon) - Didi Sukardi; Agus Abikusna; Rani Sri Imayati Rahayu (Mahkamah : Jurnal Kajian Hukum Islam, 2019)
In the process of resolving the problem of victims of marital rape or victims of forced sexual relations in marriage which is generally lay law, of course requires assistance, one of which is legal assistance. This research aims to find out the role and mechanism of legal assistance against victims of marital rape conducted by the Women Crisis Center Mawar Balqis Cirebon which is reviewed from Law Number 23 of 2004 concerning the Elimination of Domestic Violence and obstacles and efforts in legal assistance to victims of marital rape conducted by the Women Crisis Center Mawar Balqis Cirebon. The research method uses a sociological juridical approach. The results of this study, namely 1) Women Crisis Center Mawar Balqis Cirebon has a very important role in carrying out legal assistance to victims of marital rape who are unfamiliar with the law. 2) the legal assistance mechanism for victims of marital rape is carried out on the basis of the wishes of the victims. 3) obstacles in carrying out legal assistance to victims of marital rape, namely obstacles arising from victims, families, the community, the state and the existence of inappropriate understanding of religious teachings. Then, the efforts made are by reviewing the arguments that textually corner one party and the existence of education (learning).